Signed, Sealed, and Delivered with Trust: Non-Resident Citizens’ Experiences of Newly Adopted Postal Voting - Wass, Hanna; Peltoniemi, Johanna; Weide, Marjukka; Nemčok, Miroslav (Frontiers in Political Science, 2021)
The COVID-19 pandemic has made it clear that the traditional “booth, ballot, and pen” model of voting, based on a specific location and physical presence, may not be feasible during a health crisis. This situation has highlighted the need to assess whether existing national electoral legislation includes enough instruments to ensure citizens’ safety during voting procedures, even under the conditions of a global pandemic. Such instruments, often grouped under the umbrella of voter facilitation or convenience voting, range from voting in advance and various forms of absentee voting (postal, online, and proxy voting) to assisted voting and voting at home and in hospitals and other healthcare institutions. While most democracies have implemented at least some form of voter facilitation, substantial cross-country differences still exist. In the push to develop pandemic-sustainable elections in different institutional and political contexts, variation in voter facilitation makes it possible to learn from country-specific experiences. As accessibility and inclusiveness are critical components of elections for ensuring political legitimacy and accountability these lessons are of utmost importance. In this study, we focus on Finland, where the Parliament decided in March 2021 to postpone for two months the municipal elections that were originally scheduled to be held on April 18. Although the decision was mostly justified by the sudden and dramatic daily increase in new COVID-19 infections, the inability to guarantee the opportunity to vote for those in quarantine was included among the likely risks. The failure to organize health-safe voting procedures to accommodate the original schedule emphasizes a certain paradox in the Finnish electoral legislation: caution in introducing new facilitation instruments has led to lower levels of preparedness and flexibility in crisis situations. Although a forerunner in implementing extensive advance voting opportunities, Finland has only recently introduced postal voting, which is restricted to voters living abroad. Hence, we ask: what can be learned from this form of convenience voting if expanded to all voters to enhance the sustainability of elections? Our analyses are based on a survey conducted among non-resident voters (n = 2,100) after the 2019 parliamentary elections in which postal voting from abroad was allowed for the first time. Our results show that whereas trust in the integrity of postal voting is quite high, various efforts needed from individual voters substantially increase the costs of postal voting. Postal operations also raise concerns. Furthermore, voters felt that requiring two witnesses made postal voting cumbersome, an issue that needs to be resolved, particularly if applying postal voting in the context of a pandemic. The Finnish case constitutes a concrete example of a situation in which voter facilitation targeted to a particular segment of society may become a testbed for electoral engineering that will improve voting opportunities for everyone.